Indic Manuscript Cultures through the Ages - Cuneo, Daniele; Formigatti, Camillo Alessio; Vergiani, Vincenzo (2017)
Stemming from the Sanskrit Manuscripts Project that ran in Cambridge (UK) in 2011-2014 and led to the cataloguing and partial digitization of the rich collections of South Asian manuscripts in the University Library, these essays explore the manuscript culture of India and beyond – Nepal, Cambodia, Tibet – from a variety of angles: books as artefacts, works of art, commodities, staples of tradition, and of course as repositories of knowledge.